An Unusual Retinal Vessel Modification in Patients Affected by JIA-Uveitis with a Follow-Up Longer Than 16 Years - Alessandro Abbouda; Irene Abicca; Simone Bruschi; Federico Ricci; Gianluca Aloe; Maria Pia Paroli (Case Reports in Ophthalmological Medicine)
Purpose. To report unusual and rare clinical changes of retinal vessel pattern in a series of patients affected by Juvenile Idiopathic Arthritis (JIA) uveitis with a follow-up longer than 16 years. Methods. A series of three patients with JIA-uveitis followed at the University of Rome “Sapienza” from 1998 to 2014 were reported. The retinal vessels were analyzed with fluorescein angiography using Heidelberg Retinal Angiogram-2 (HRA-2; Heidelberg Engineering GmBH, Dossenheim, Germany) and the Topcon TRC-50LX retinal camera (Topcon Europe, The Netherlands). A Spectralis Domain OCT (SD-OCT) (Spectralis Family Heidelberg, Germany) was performed to evaluate vessel anatomy. Results. Fundus photography showed sheathed vessels localized around the optic disc in every case. Angiography revealed a normal physiology of vessel walls and flow; no sheathing or leakage of dye was observed. SD-OCT demonstrated reflective vessel walls. Vessel lumen appeared patent, and the normal “hourglass configuration” was blurred, but identifiable. Conclusions. Vessel modifications observed in long-standing JIA-uveitis are not signs of vascular inflammation and are not associated to hypoperfusion. In these cases, ophthalmologists should avoid further invasive investigation and should consider introducing SD-OCT as a routine method to evaluate the vessel changes during the follow-up.